Swamy's compilation of central civil services (CCS), classification control and appeal (CCA) rules - Muthuswamy; Brinda; Sanjeev (Chennai Swamy publishers, 2023)
This book contain an up-to-date treatise incorporating government of India's orders arranged under the relevant rules.
Keywords: CCS, CCA rules